Tribo-Mechanical Properties of the Antimicrobial Low-Density Polyethylene (LDPE) Nanocomposite with Hybrid ZnO-Vermiculite-Chlorhexidine Nanofillers - Čech Barabaszová, Karla; Holešová, Sylva; Hundáková, Marianna; Kalendová, Alena (Polymers, 2020)
Materials made from low-density polyethylene (LDPE) in the form of packages or catheters are currently commonly applied medical devices. Antimicrobial LDPE nanocomposite materials with two types of nanofillers, zinc oxide/vermiculite (ZnO/V) and zinc oxide/vermiculite_chlorhexidine (ZnO/V_CH), were prepared by a melt-compounded procedure to enrich their controllable antimicrobial, microstructural, topographical and tribo-mechanical properties. X-ray diffraction (XRD) analysis and Fourier transform infrared spectroscopy (FTIR) revealed that the ZnO/V and ZnO/V_CH nanofillers and LDPE interacted well with each other. The influence of the nanofiller concentrations on the LDPE nanocomposite surface changes was studied through scanning electron microscopy (SEM), and the surface topology and roughness were studied using atomic force microscopy (AFM). The effect of the ZnO/V nanofiller on the increase in indentation hardness (HIT) was evaluated by AFM measurements and the Vickers microhardness (HV), which showed that as the concentration of the ZnO/V nanofiller increased, these values decreased. The ZnO/V and ZnO/V_CH nanofillers, regardless of the concentration in the LDPE matrix, slightly increased the average values of the friction coefficient (COF). The abrasion depths of the wear indicated that the LDPE_ZnO/V nanocomposite plates exhibited better wear resistance than LDPE_ZnO/V_CH. Higher HV and HIT microhardness values were measured for both nanofillers than the natural LDPE nanocomposite plate. Very positive antimicrobial activity against S. aureus and P. aeruginosa after 72 h was found for both nanofiller types.
Keywords: LDPE nanocomposites; structural phase characterization; antimicrobial hybrid nanofillers; tribo-mechanical properties; wear resistance